Stakeholders’ Perspectives on Rationing COVID-19 Vaccines Amidst Extreme Scarcity: A Qualitative Study - Barugahare, John; Kwagala, Betty; Ochieng, Joseph (Research Square, 2021)
In the context of scarce health-resources robust priority setting for access to existing interventions is critical for at least two reasons: ensuring efficient use of resources, and equitable access to existing interventions. This need is more urgent, and its achievement more intractable in severely resource-constrained health systems, of Low and Middle Income Countries, such as Uganda. COVID-19 pandemic and the resulting need for large-scale and immediate vaccination amidst extreme scarcity of vaccines in Uganda necessitated an exploration of stakeholders’ perspectives on the country’s priority setting for access to COVID-19 vaccines. We aimed at exploring stakeholders’ perspectives on priority setting for COVID-19 vaccination in Ugandan. Methods: We conducted key informant and in-depth interviews with key stakeholders in the COVID-19 intervention including public health experts, clinicians, policy makers, human rights experts, bioethicists, legal fraternity, biomedical scientists and members from the general public. Stakeholders’ views were sought on the status of official guidelines for rationing COVID-19 vaccines; who they thought should get priority for vaccination and why; and what the process of setting such priorities should involve. Data were transcribed and analysed thematically using NVivo software (QSR international 2020). Results: There was concern about lack of clarity regarding context-specific guidance on priorities COVID- 19 vaccination. This concern was corroborated by the fact that national guidelines for COVID-19 vaccination are still in draft form and inaccessible to the public. Regarding who should get priority and why, dominant views indicated more concern for efficiency-cum-effectiveness at controlling the spread of the virus, although further probing revealed that some of these views were partly motivated by equity concerns. Most respondents felt that the process of developing the needed guidelines should have employed a bottom-up approach involving rigorous community engagement.
Keywords: health-resources; COVID-19; vaccination; Uganda